An Analysis of the Barkley Deficits in Executive Functioning Scale in a College Population: Does It Predict Symptoms of ADHD Better Than a Visual-Search Task?. (May 2017) - Dehili, Vincent Malik; Prevatt, Frances; Coffman, Theodora P.
Objective: Executive functioning (EF) deficits have been associated with ADHD. However, disagreement exists concerning the extent to which cognitive tests of EF accurately reflect a diagnosis of ADHD. Barkley developed the Barkley Deficits in Executive Functioning Scale (BDEFS) by categorizing the meta-construct of EF into five subdomains. This study investigated the incremental validity of the BDEFS in predicting symptoms of ADHD compared with a visual-search task. We also investigated patterns among the five BDEFS domains.Method: One hundred and sixteen college students completed a visual-search task and the BDEFS and reported on their symptoms of ADHD.Results: (a) BDEFS total scores significantly predicted total ADHD symptoms, whereas the visual-search task failed to predict ADHD symptoms. (b) The BDEFS demonstrated significant correlations with symptoms of ADHD in expected patterns.Conclusion: This study provides evidence of validity for the BDEFS in a college sample.